2013
DOI: 10.1093/infdis/jit421
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcal Enterotoxin B–Specific Monoclonal Antibody 20B1 Successfully Treats Diverse Staphylococcus aureus Infections

Abstract: mAb 20B1, an SEB-neutralizing mAb, is effective against MRSA infection. mAb 20B1 protects against lethal sepsis and reduces skin tissue invasion and deep-abscess formation. The mAb penetrates well into the abscess and binds to SEB. It affects the outcome of S. aureus infection by modulating the host's proinflammatory immune response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 50 publications
1
50
0
Order By: Relevance
“…Although the Newman ⌬sea mutant demonstrated decreased counts within the hearts, we did not observe any obvious aortic valve vegetations from wild-type Newman, although our protocol is not an endocarditis model as valve damage is not actively induced. Neutralization of SEB also decreased abscess size using a murine thigh infection model (28). Although it is difficult to aggregate these collective findings, an overall picture is now emerging that SAg-induced inflammation contributes to the formation with S. aureus Newman (n ϭ 17), the Newman ⌬sea mutant (n ϭ 17), or the Newman ⌬sea(pSEA) mutant (n ϭ 12) from liver (A), kidneys (B), lungs (C), and heart (D) 96 h postinfection.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Although the Newman ⌬sea mutant demonstrated decreased counts within the hearts, we did not observe any obvious aortic valve vegetations from wild-type Newman, although our protocol is not an endocarditis model as valve damage is not actively induced. Neutralization of SEB also decreased abscess size using a murine thigh infection model (28). Although it is difficult to aggregate these collective findings, an overall picture is now emerging that SAg-induced inflammation contributes to the formation with S. aureus Newman (n ϭ 17), the Newman ⌬sea mutant (n ϭ 17), or the Newman ⌬sea(pSEA) mutant (n ϭ 12) from liver (A), kidneys (B), lungs (C), and heart (D) 96 h postinfection.…”
Section: Discussionmentioning
confidence: 92%
“…Early work by Tarkowski and colleagues has demonstrated a pathogenic role of TSST-1 for the onset of dermatitis, arthritis, and septic mortality in mice (24,25). In addition, vaccination with SAg toxoids or neutralization of SAgs with monoclonal antibodies has prevented or reduced mortality from experimental S. aureus sepsis (26)(27)(28). Rabbits are particularly sensitive to the effects of SAgs; using this animal species, deletion of the gene encoding SEl-X from S. aureus USA300 demonstrated reduced mortality from necrotizing pneumonia (29), and deletion of the gene encoding staphylococcal enterotoxin C (sec) from S. aureus MW2 prevented mortality in a rabbit model of sepsis/infective endocarditis (30).…”
mentioning
confidence: 99%
“…Several studies demonstrate that neutralization of SAgs with drugs or Abs improves outcomes in both intoxication and infection models (39)(40)(41)(42)(43). Specifically, a recent study from our laboratory performed with MAbs specific to SEB provides encouraging data with respect to the development of such Abs as adjunctive therapy for complicated S. aureus infections (44). Given that several anti-infective MAbs are now FDA licensed, more efforts should be focused on developing additional MAbs as therapeutics to neutralize SEs (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…8 While SAgs are best studied for their role in TSS and food poisoning, several lines of evidence suggest that SAgs also play a critical role in S. aureus disease even in the absence of classical TSS. Over the past few years several groups have reported partial protection against S. aureus infections in various models using vaccines or antibodies against SEB, 9 SEA, 10 TSST-1, 11 and SEC. 12 In this issue of Virulence, Aguilar et al 13 report 2 monoclonal antibodies that neutralize SEK, a superantigen produced by most isolates of USA 300, the MRSA clone that is currently circulating and is responsible for most cases of S. aureus invasive disease in the US.…”
mentioning
confidence: 99%
“…This group had previously shown that an SEB-producing MRSA strain was highly virulent in sepsis, skin infection, and a thigh muscle infection models and that an anti-SEB mAb or SEB immunization provided partial to complete protection in these models. 9 In the current paper, Aguilar et al also evaluated the efficacy of the combination of an anti-SEB mAb and their anti-SEK mAb against a strain (W-132) that produces both toxins. However, the combination of the 2 mAbs failed to protect against W-132 infection.…”
mentioning
confidence: 99%